2021
DOI: 10.5114/aoms/128103
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mechanism of intestinal microbiota involved in Guillain-Barre syndrome and with Bifidobacterium intervention

Abstract: IntroductionGuillain-barre syndrome (GBS) is an acute immune-mediated polyneuropathy, involving the peripheral nervous system. The pathogenicity of GBS lies on Th17/Treg imbalance which may be affected by intestinal microbiota. From the previous study, treatment with Bifidobacterium infantis (B. infantis) significantly improved the symptoms of experimental autoimmune neuritis (EAN) through reducing the levels of IL-17A. In the present study, we aimed to further investigate the pathogenic mechanisms of intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this regard, studies have shown that probiotics (e.g., Lactobacillus helveticus R0052, Bifidobacterium infantis ) may improve GBS immune balance by reducing the most common bacteria associated with GBS, namely Campylobacter jejuni, Escherichia , and Coprococcus ( 21 ). Besides, probiotic Bifidobacterium infantis administration improves the imbalance of Th cell subsets (Th1, Th2, Th17) and promotes Treg cells' levels, thereby ameliorating GBS symptoms ( 22 , 23 ).…”
Section: Use Of Probiotics As Regulators Of Microbial Interaction Net...mentioning
confidence: 99%
“…In this regard, studies have shown that probiotics (e.g., Lactobacillus helveticus R0052, Bifidobacterium infantis ) may improve GBS immune balance by reducing the most common bacteria associated with GBS, namely Campylobacter jejuni, Escherichia , and Coprococcus ( 21 ). Besides, probiotic Bifidobacterium infantis administration improves the imbalance of Th cell subsets (Th1, Th2, Th17) and promotes Treg cells' levels, thereby ameliorating GBS symptoms ( 22 , 23 ).…”
Section: Use Of Probiotics As Regulators Of Microbial Interaction Net...mentioning
confidence: 99%
“…His significant contribution to the 1916 publication and the introduction of myographic studies in the diagnostic approach of AIDP should be crowned with the use of his name in the eponym of the syndrome. Currently, the eponym composed of two surnames is still most often used, thus maintaining Strohl’s ostracism [ 17 ]. However, despite the controversy caused by Strohl’s omission, the use of the tripartite eponym (Guillain-Barré-Strohl syndrome) continues to be fully valid [ 18 ].…”
mentioning
confidence: 99%